Self-assembly method based on tetraphenyl ethylene-carbazole chiral material

By co-assembling tetraphenylethylene-carbazole materials and chiral limonene, a complex hierarchical spiral flower-like assembly was constructed, which solved the problem of improving the performance of CPL self-assembled materials of carbon borane groups and realized the development of high-performance circularly polarized luminescent materials.

CN120774946APending Publication Date: 2025-10-14NANJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510901480.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-01
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

The CPL performance improvement of existing carbon borane group self-assembly materials is relatively limited, the assembly method is single, and the reported glum value of boron cluster materials is low. There is an urgent need to develop new structural systems to expand the application boundaries.

Method used

A non-chiral fluorescent material tetraphenylethylene-carbazole material was designed to be co-assembled with chiral limonene. Through weak interaction regulation, a flower-like assembly with a complex hierarchical helix was constructed. The tetraphenylethylene unit with a propeller-shaped dynamic conformation and the DA-type conjugated skeleton of carbazole were introduced, and precise control was achieved by combining variables such as solvent composition, temperature gradient and enantiomeric excess value.

Benefits of technology

The CPL performance of the material was significantly improved, the chiral signal transmission effect was significant, the glum value was increased to the order of 10-2, precise control of the supramolecular assembly path was provided, and a high-performance circularly polarized luminescent material was constructed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120774946A_ABST
    Figure CN120774946A_ABST
Patent Text Reader

Abstract

The invention discloses a chiral self-assembly material based on a tetraphenyl ethylene-carbazole material and a self-assembly method of the chiral self-assembly material. A carbazole unit is used as an electron donor (D) to construct a D-A type conjugated skeleton with a carborane electron acceptor (A), and a tetraphenyl ethylene unit with propeller-shaped dynamic conformation is introduced; the rigid plane structure of carbazole endows the molecule with a significant pi-pi stacking tendency, and the flexible conformation of tetraphenyl ethylene provides dynamic adjustability for the system; through co-assembly with chiral limonene, the successful coupling between the chiral limonene and molecules increases the orderliness of molecular stacking from the macroscopic level, greatly improves the circular polarization value, provides a powerful structural model and theoretical basis for constructing the structure-function relationship between the structure of the organic supramolecular self-assembly body and circular polarization fluorescence, and has broad application prospects. And a novel strategy is provided for designing a novel organic circularly polarized photoelectric material.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of chiral self-assembly materials, in particular to a chiral self-assembly material based on tetraphenylstyrene-carbazole and a self-assembly method thereof. BACKGROUND

[0002] Supramolecular chemistry constructs dynamic functional systems through intermolecular non-covalent interactions (such as hydrogen bonding, π-π stacking, electrostatic interaction, etc.), revealing the chemical nature of the spontaneous organization of molecules into ordered structures. This field is deeply interrelated with the study of chiral materials, which is a frontier topic in chemistry, physics, biology and nanoscience, and has unique significance at the molecular and supramolecular scales. Chirality is not only a core feature of life systems, but also has key value in drug design and functional material development - molecular chirality directly affects the biological activity and metabolic pathway of drugs, and supramolecular chirality transmission provides a new paradigm for constructing dynamic response materials. In recent years, self-assembly strategies based on supramolecular chemistry have become a core method for developing chiral nanomaterials. By precisely regulating non-covalent interactions such as hydrogen bonding, π-π stacking, ion-dipole interaction, electrostatic interaction, acid-base interaction and van der Waals force, researchers can directionally construct nanometer or micrometer-sized supramolecular systems with specific functions. The reversibility of these weak forces endows the material with dynamic response capability, such as inducing structural reorganization through temperature or solvent polarity changes, thereby realizing real-time regulation of material morphology and function.

[0003] To obtain high-performance CPL (Circularly Polarized Luminescence) active materials, supramolecular self-assembly systems have become a research hotspot. Self-assembly strategies can significantly enhance the optical properties of materials by precisely regulating the arrangement of structural units. For example, by embedding inorganic materials in a chiral supramolecular matrix, CPL activity can be imparted through non-covalent interactions without complex chiral modification. This co-assembly system not only simplifies the lengthy steps in traditional synthesis, but also provides a new way to flexibly regulate the chirality symbol and emission wavelength of the CPL signal. By adjusting the ratio or interaction type of components in the assembly system, researchers can directionally optimize the emission asymmetry factor and quantum efficiency.

[0004] Self-assembly not only amplifies the circular polarization intensity of existing CPL materials, but also imparts CPL activity to non-chiral chromophores, providing a universal method for developing new CPL materials. Based on this effective method, various organic and inorganic materials can be embedded in a chiral host, thereby generating a large number of CPL active materials.

[0005] The three-dimensional cage-like skeleton of carborane group provides innovative strategies for the construction of multi-scale chiral assemblies by virtue of its three-dimensional cage-like skeleton and multi-dimensional non-covalent network (such as B-H···π interaction, hydrogen bond and van der Waals force synergy). This structure not only realizes the multi-scale transmission of chiral information by regulating the molecular packing mode (such as helix dislocation or interlayer twist) through steric electronic effect, but also enhances the exciton confinement effect to improve the quantum yield, and dynamically couples with the chiral conformation to give the system a significant circularly polarized luminescence response. The precise constraint of the rigid skeleton on the intermolecular twist angle makes the carborane hybrid system more easily form complex superstructures such as helix and fractal under solvent mediation, breaking through the limitations of traditional assemblies relying on a single force and opening up a new path for the design of environmentally responsive photonic materials.

[0006] The unique advantages of carborane in stabilizing supramolecular structures, regulating energy level distribution and enhancing chiral optical response, but the controllability mechanism of the self-assembly process and the analysis of the structure-activity relationship still need to be further explored by combining multi-scale characterization and theoretical simulation. Although the carborane unit exhibits excellent performance in the field of luminescence by amplifying the magnetic dipole moment of the TICT (intramolecular charge transfer) state and regulating the conformation-dependent emission, the current systematic study on circularly polarized luminescent materials is still insufficient, and new structure systems need to be developed to expand the application boundary.

[0007] Designing non-chiral carborane derivative luminescent materials and self-assembling with chiral small molecules can avoid the lengthy chiral material synthesis process, and can also improve the CPL and g lum value of the product by one level, but the current research on the chirality of carborane-based luminescent materials is less, and the reported boron cluster materials have low g lum value, and the assembly method is single. In order to solve this problem, the present application develops new boron cluster luminescent materials, and designs new self-assembly schemes according to the characteristics of the materials to improve the CPL performance of the materials. SUMMARY

[0008] To solve the problems raised in the background art, the present application provides a chiral self-assembly material and method based on tetraphenyl ethylene-carbazole material. The present application discloses a new non-chiral fluorescent material, which constructs a D-A type conjugated skeleton with a carbazole unit as an electron donor (D) and a carborane electron acceptor (A), and introduces a tetraphenyl ethylene unit with a dynamic conformation of propeller. The rigid planar structure of carbazole gives the molecule a significant π-π stacking tendency, while the flexible conformation of tetraphenyl ethylene provides dynamic adjustability to the system. By co-assembling with chiral limonene, a flower-shaped assembly with complex helical levels can be constructed at 15-50°C through the competitive regulation of weak interactions (van der Waals force, C-H···π, etc.), and the strong CPL signal (luminescence asymmetry factor g lum up to 10 -2The results of the circular dichroism (CD) spectra of the assembly and the corresponding monomer (Figure 6) confirmed the effective transfer of chirality from the solvent to the assembly. Further systematic studies showed that the external environmental parameters significantly regulated the CPL performance of the assembly: by adjusting the solvent composition, temperature gradient, and enantiomeric excess value (χ), it was found that as the temperature increased, the |χ| value increased, and the system tended to form flower-like aggregates with multi-level characteristics. This phenomenon revealed that environmental factors could achieve precise regulation of the supramolecular assembly path by affecting the balance of intermolecular forces.

[0009] To achieve the above object, the present application provides the following technical scheme:

[0010] The present application provides a tetraphenylstyrene-carbazole material, as shown in formula 1:

[0011]

[0012] The present application also provides a preparation method of the tetraphenylstyrene-carbazole material, and the preparation method comprises the following steps:

[0013] (1) Synthesis of intermediate product 2: under light protection and nitrogen protection, the drug 1, CuI catalyst and tetraphenylphosphine palladium catalyst are added to a reaction container, vacuumized and filled with nitrogen for at least three times, anhydrous and oxygen-free triethylamine and phenylacetylene are added, the temperature is increased to 70-75 DEG C, and the reaction is carried out in the dark for 8-12 hours. The reaction solution is cooled to room temperature, the solvent is removed by rotary evaporation, the residue is extracted with dichloromethane three times, the organic phase is combined, and the solvent is removed by rotary evaporation. The product 2 is separated and purified by column chromatography;

[0014]

[0015] (2) Synthesis of intermediate product 3: carbon borane is placed in a reaction container, vacuumized, and a mixed solvent of N,N-dimethyl aniline and toluene is injected into the reaction container after nitrogen is blown. The reaction is carried out under light protection and stirring at room temperature for 25-30 minutes, and the temperature is increased to 70-75 DEG C. The reaction is carried out for 1-2 hours, the temperature is decreased to 35-40 DEG C, the dried intermediate product 2 is dissolved in toluene, and the reaction is carried out after nitrogen is blown. The temperature is increased to 110-120 DEG C, and the reaction is carried out for 8-12 hours. After the reaction is completed, the temperature is decreased to room temperature, the solvent is removed by rotary evaporation, the residue is extracted with dichloromethane, the organic layer is separated, the solvent is removed by rotary evaporation, and the product 3 is separated and purified by column chromatography to obtain a white powder;

[0016]

[0017] (3) Synthesis of the target product: under the protection of light and nitrogen, the drug 3, CuI catalyst and tetraphenylphosphonium palladium catalyst are added to the reaction container, vacuumed and filled with nitrogen for at least three times, anhydrous and oxygen-free triethylamine or a mixed solution of tetrahydrofuran and triethylamine, phenylacetylene are added, the temperature is raised to 70-75 DEG C, and the reaction is carried out in the dark for 8-12 h; the reaction solution is cooled to room temperature, the solvent is removed by rotary evaporation, the residue is extracted with dichloromethane for three times, the organic phase is combined, and the solvent is removed by rotary evaporation; column chromatography is used for separation and purification to obtain the target product tetraphenylstyrene-carbazole material;

[0018]

[0019] Further, in step (1), the molar ratio of the drug 1 and phenylacetylene is 1:13-14, the mass percentage of CuI catalyst and drug 1 is 5%, the mass percentage of tetraphenylphosphonium palladium catalyst and drug 1 is 10%, the mass-volume ratio of drug 1 and triethylamine or a mixed solution of tetrahydrofuran and triethylamine is 1:50-55, and the ratio of tetrahydrofuran to triethylamine in the mixed solution of tetrahydrofuran and triethylamine is 1:3.

[0020] In step (3), the molar ratio of the drug 3 and phenylacetylene is 1:13-14, the mass percentage of CuI catalyst and drug 3 is 5%, the mass percentage of tetraphenylphosphonium palladium catalyst and drug 3 is 10%, the mass-volume ratio of drug 3 and triethylamine or a mixed solution of tetrahydrofuran and triethylamine is 1:50-55, and the ratio of tetrahydrofuran to triethylamine in the mixed solution of tetrahydrofuran and triethylamine is 1:3.

[0021] Further, in step (2), the molar ratio of carborane and intermediate product 2 is 2-3:1, the molar ratio of carborane and N,N-dimethylaniline is 1:4-5, and the mass-volume ratio of N,N-dimethylaniline and toluene is 1:25.

[0022] The application provides a chiral self-assembled material based on a tetraphenylstyrene-carbazole material, which is prepared by self-assembly of a chiral reagent and an achiral fluorescent molecule.

[0023] The achiral fluorescent molecule is the tetraphenylstyrene-carbazole material as described above, and its structure is shown in formula 1.

[0024] The chiral reagent is limonene.

[0025] Further, the chiral reagent further includes β-pinene, S / R-carvone, vitamin D2 and valencene.

[0026] The application further provides a self-assembly method of the chiral self-assembled material based on the tetraphenylstyrene-carbazole material.

[0027] S01, dissolving the achiral fluorescent molecule (tetraphenyl ethene-carbazole material) in chloroform to obtain solution A

[0028] S02, mixing S-limonene and R-limonene to obtain a limonene solution with an excess value χ, i.e., solution B;

[0029] The calculation formula of χ value is as follows:

[0030] Wherein, S is the volume of S-limonene, and R is the volume of R-limonene;

[0031] S03, uniformly mixing solution A and solution B, adding ethanol and chloroform and stirring uniformly, and standing at 15-25℃ until the appearance of aggregates, i.e., obtaining a chiral self-assembly material.

[0032] Further, in step S01, the concentration of the achiral fluorescent molecule in solution A is 7.1-7.2 mg / mL.

[0033] Further, in step S02, the ratio of S to R is ±100%.

[0034] Further, in step S03, the volume ratio of the total volume of solution A and chloroform to the volume of ethanol is 1:2-3.

[0035] Further, in step S03, the volume ratio of solution A to solution B is 1:1-1.2.

[0036] Compared with the prior art, the present application has the following beneficial effects:

[0037] The achiral fluorescent compound is synthesized, and tests show that the achiral fluorescent compound has good thermal stability, electrochemical property and crystallinity. The chiral limonene is selected as a chiral template to self-assemble with the achiral fluorescent compound at different temperatures and in different solvents to form two morphologies of two-dimensional sheet structure and complex three-dimensional flower-like structure. The rigidity, electron-rich property and hydrophobicity of the achiral fluorescent compound molecule brought by borane are deeply studied by tests such as scanning electron microscopy, fluorescence, circular polarization, SC-XRD and powder XRD to explore the internal mechanism of chiral transfer of chiral limonene and achiral fluorescent compound. The successful coupling between the chiral limonene and the achiral fluorescent compound molecules increases the order of molecular stacking from a macroscopic level, greatly improves the circular polarization value, provides a powerful structural model and theoretical basis for the structure-activity relationship between the structure of the organic supramolecular self-assembly and the circular polarization fluorescence, and provides a new strategy for designing new organic circular polarization photoelectric materials. BRIEF DESCRIPTION OF DRAWINGS

[0038] Figure 1P-XRD curve of C-1 substance;

[0039] Figure 2 Electrochemical profile of C-1 (a) CV; (b) GCD;

[0040] Figure 3 (a) (c) SEM images of flower-like structure assembled by C-1 and S-limonene at 15℃; (b) (d) SEM images of the fragments of the flower-like structure assembly after ultrasonic treatment;

[0041] Figure 4 Image of the assembly of C-1 and S-limonene under the irradiation of fluorescence microscope at 405 nm excitation wavelength;

[0042] Figure 5 Crystal structure of the assembly of C-1 and S-limonene; (a-c) are the packing diagrams of S-C-1 crystal along a, b, c axis direction; (d) is the bond length bond angle of asymmetric unit; (e) is the crystal packing structure and intermolecular interaction of the multimer; (f) is the interlayer distance;

[0043] Figure 6 SEM images of petal-like morphology assembled by C-1 and S-limonene at 15℃ under different volume ratios of chloroform and ethanol; (a-c) V CH3OH / V EtOH = 1 / 2 to form flower-like morphology; (d-f) V CH3OH / V EtOH = 1 / 3 to form flower-like morphology;

[0044] Figure 7 (a) V CH3OH / V EtOH = 1 / 2 condition; (b) V CH3OH / V EtOH = 1 / 3 condition;

[0045] Figure 8 Spectroscopic tests of the flower-like structure assembly generated by C-1 and S-limonene under different solvent ratios; (a) PL test; (b) P-XRD; (c) CPL test; (d) g lum value;

[0046] Figure 9 (a) (c) SEM images of flower-like structure assembled by C-1 and R-limonene; (b) (d) SEM images of the fragments of the flower-like structure assembly after ultrasonic treatment;

[0047] Figure 10 Image of the assembly of C-1 and R-limonene under the fluorescence microscope;

[0048] Figure 11 The crystal structure of C-1 and R-limonene assembly; (a-c) are the packing diagrams of R-C-1 crystal along a, b, c axis direction; (d) is the bond length bond angle of asymmetric unit; (e) is the interlayer distance; (f) is the crystal packing structure of multimer and intermolecular interaction;

[0049] Figure 12 The SEM images of petal-like morphology of C-1 and R-limonene assembly at 15℃ under different solvent ratios; (a-c) are the V CH3OH / EtOH The flower-like morphology formed under =1 / 2 condition; (d-f) are the V CH3OH / EtOH The flower-like morphology formed under =1 / 3 condition;

[0050] Figure 13 The particle size statistical distribution diagram of petal-like assembly of C-1 and R-limonene; (a) is the V CH3OH / EtOH The particle size statistics of flower-like aggregate formed under =1 / 2 condition; (b) is the V CH3OH / EtOH The particle size statistics of flower-like aggregate formed under =1 / 3 condition;

[0051] Figure 14 The spectral test of petal-like structure assembly of C-1 and R-limonene generated under different solvent ratios; (a) is the PL test; (b) is the P-XRD; (c) is the CPL test; (d) is the g lum value;

[0052] Figure 15 The infrared test data of assembly of C-1 and S / R limonene; (a) is S-C-1; (b) is the enlarged infrared spectrum of S-C-1; (c) is R-C-1; (d) is the enlarged infrared spectrum of R-C-1;

[0053] Figure 16 The TGA data diagram of (a) C-1 and (c) S / R configuration aggregate; the DSC data diagram of (b) C-1 and (d) S / R configuration aggregate;

[0054] Figure 17 The SEM photos of particles obtained by assembling C-1 and limonene under different nucleation temperature tn and enantiomeric excess χ conditions;

[0055] Figure 18 The spectral test of assembly of C-1 and limonene under different nucleation temperature tn and enantiomeric excess χ conditions; (a-c) are the PL, CPL, g lum value data diagrams of assembly produced at 30℃; (d-f) are the PL, CPL, g lumValue data graph; (g-i) Assembled PL, CPL, g lum Value data graph; P-XRD test on assembled at (j) 30℃; (k) 40℃; (l) 50℃;

[0056] Figure 19 SEM pictures of the assembly of compound C-1 with five chiral reagents; (a) β-pinene; (b) S-carvone; (c) R-carvone; (d) Vitamin D2; (e) Valencene;

[0057] Figure 20 Spectroscopic test of the assembly of C-1 with five chiral reagents; (a) PL test; (b) CPL test; (c) glum value. DETAILED DESCRIPTION

[0058] The technical solutions in the embodiments of the present application will be apparently and completely described below with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all the other embodiments obtained by those skilled in the art without creative labor fall within the protection scope of the present application.

[0059] Embodiment 1

[0060] Self-assembly of a chiral self-assembled material based on the tetraphenylstyrene-carbazole material (achiral fluorescent molecule C-1) prepared in Embodiment 7.

[0061] Chiral limonene was selected to self-assemble with the achiral fluorescent molecule C-1 prepared in Embodiment 7, and the specific experimental design is as follows:

[0062] Solution A: 7 mg of the achiral fluorescent molecule C-1 prepared in Embodiment 7 was weighed and added into 1 mL of chloroform to prepare a stock solution with a concentration of 7 mg / mL.

[0063] Solution B: S-limonene as a limonene solution. That is, a χ = +100% solution obtained by mixing 100 μL of S-limonene and 0 μL of R-limonene.

[0064] The calculation formula of χ value is as follows:

[0065]

[0066] Wherein, S and R respectively represent the volume of S-limonene and R-limonene;

[0067] Chiral limonene self-assembly with achiral fluorescent molecules: 100 μL of solution A and 100 μL of solution B were mixed in a reaction bottle, 125 μL of chloroform and 675 μL of ethanol (1 / 3) were added, and after stirring, the mixture was placed at 15°C until the aggregates appeared.

[0068] At the kinetic regulation interval (15°C), a multi-level flower-like structure with a diameter of about 513 μm was formed Figure 3 The middle a, c is composed of helical stacking of triangular nanosheets. Slow evaporation of solvent under low temperature conditions forms a concentration gradient field, prolongs the kinetic regulation window of the assembly process, and the initially formed nanosheet unit releases the interfacial tension by edge curling Figure 3 Middle b, d, then undergoes an iterative process of dissolution-recrystallization under the induction of chiral molecules, gradually optimizes the helical matching angle between nanosheets, and finally forms a thermodynamically metastable multi-level topological structure.

[0069] By ultrasonic crushing of the multi-level assembly Figure 3 Middle b), the triangular nanosheet unit and its twisted characteristics are observed to remain in the fragments, confirming the existence of dynamic interfacial reconstruction behavior in the assembly process. The helical morphology of the nanobelt Figure 3 Middle d) further verifies the helical stacking mechanism of the nanosheet unit driven by the intermolecular torque effect of chiral limonene, which is highly consistent with the theoretical model. This research reveals that temperature can precisely manipulate the dimension and topological structure of the assembly by regulating the competition between solvent evaporation kinetics and molecular diffusion rate.

[0070] Laser scanning confocal fluorescence microscopy equipped with a 405 nm blue-violet laser excitation source was used to perform fluorescence-transmission dual-mode imaging characterization of the aggregates after ethanol washing and drying Figure 4 ). The flower-like multi-level structure emits blue light. Since the central region is more than 50 μm thick, it forms an optical barrier, and only the edge nanosheet assembly unit (about 18 μm thick) can be penetrated by the excitation light. Its transmission image reveals that the structure is formed by a large number of nanosheets through helical stacking to form a three-dimensional topology. This multi-level assembly leads to a relatively low overall fluorescence intensity, indicating that the exciton coupling between nanosheets is weakened due to the helical twist.

[0071] In order to study the coupling mechanism of self-assembly of C-1 and S-limonene and its chiral regulation effect, the present invention carried out X-ray single crystal diffraction (XC-XRD) analysis on the assembly SC-1 of the self-assembly of C-1 and S-limonene as the research object. First, the single crystal sample was filtered and dried for pretreatment, and then the absolute configuration was determined using a Bruker SMARTAPEX (II)-CCD single crystal diffractometer equipped with a copper palladium light source, and the original crystallographic data were successfully obtained. After the data was restored by APEX3 software, the results were imported into the Olex2 program system for structural analysis, in which three-dimensional structure reconstruction was achieved by hydrogen atom introduction and differential Fourier transform technology, and the data was iteratively optimized in combination with the least squares refinement strategy of the ShelXL program, and finally the crystallographic information file was obtained. All crystal structure schematics in the study were constructed based on the Mercury software platform, and the relevant crystallographic parameters have been systematically organized in the SC-1 crystal data report in Table 1.

[0072] Table 1S-C-1 Single Crystal Data Report

[0073]

[0074] Stacking diagram from three directions of a, b, and c axis ( Figure 5 As can be seen from (a-c), the crystal presents a highly ordered three-dimensional arrangement pattern in space. Figure 5 (d) shows that the asymmetric unit of the crystal contains C-1 molecules and limonene molecules, which are tightly bound by BH···HC interactions. The distance between the methyl hydrogen of limonene and the hydrogen atom of carborane is This value is in the critical range between strong van der Waals interaction and weak hydrogen bonding, indicating the key regulatory role of CH···HB / C interaction in molecular assembly. The two CC bond lengths in the carborane structure are 1.70 and Significantly longer than standard single bonds Its abnormal elongation is due to the inherent tension of the cage-like skeleton. At the same time, the benzene ring of the tetraphenylethylene skeleton undergoes significant twisting, with dihedral angles of -51.77° and 133.66° respectively. This asymmetric twist not only maintains the π-π stacking ability through partial planarization, but also releases the intramolecular steric hindrance through large bending, forming a dynamic conformation that adapts to intermolecular interactions. Figure 5 Figure e) shows that the weak interactions (CH···π, van der Waals forces and dispersed hydrogen bonds) between limonene hydrogen and carborane, tetraphenylethylene, etc. synergistically construct a complex interaction network. Ultimately, the molecules form a periodic layered structure along the stacking direction, and the interlayer spacing is stable at

[0075] Example 2

[0076] Other preparation steps are the same as Example 1, except that the amount of ethanol added is changed (500 μL of ethanol, 675 μL of ethanol), so as to change the total volume of solution A and chloroform / ethanol ratio, to prepare products with total volume of solution A and chloroform / ethanol = 1 / 2, 1 / 3.

[0077] The solvent ratio significantly affects the assembly hierarchical structure under kinetic control (15℃): 1 / 2 solvent system forms a dense flower-like helical structure with an average particle size of 119±3.9 μm Figure 6 a-c, Figure 7 a), the nanosheets are precisely stacked by hydrogen bonding and π-π interaction. Low temperature slows down solvent evaporation, prolongs the time of molecular dynamic rearrangement, and promotes the interface matching of nanosheet units; the assembly particle size under 1 / 3 solvent system is 176.6±9.4 μm Figure 6 d-f, Figure 7 b), the nanosheet stacking is relatively loose. The increase of ethanol ratio and the enhancement of polarity accelerate the hydrophobic-driven assembly of molecules, leading to a lack of sufficient orientation adjustment in the nanosheet stacking process and forming a metastable porous structure. In addition, all assemblies exhibit significant helical characteristics Figure 6 , revealing that chiral limonene regulates the morphology through a three-stage transmission path: 1. At the molecular scale, the asymmetric steric hindrance of S-limonene induces the helical conformation deflection of C-1 molecules. 2. At the nanoscale, the chiral torque drives the edge curling of nanosheet units, forming a helical growth template. 3. At the mesoscale, the concentration gradient field generated by solvent evaporation promotes the step-by-step stacking of nanosheets along the helical template, and finally amplifies the macroscopic chiral topological structure.

[0078] The present application aims at the optical activity of the non-chiral fluorescent molecule C-1 and the assembly of chiral limonene, and a series of tests are carried out.

[0079] The optical properties, crystallization behavior and chiral optical characteristics of the flower-like complex structure (15℃) aggregate are systematically characterized. Figure 8 (a) shows that the fluorescence emission peak of the aggregate is located at 473 nm, and the light emission color is blue. Figure 8 (b) shows that when the solvent is solution A and chloroform with a total volume / ethanol ratio of 1 / 2, the crystallinity is the best, and when the solvent is solution A and chloroform with a total volume / ethanol ratio of 1 / 3, there is a clear diffraction peak, indicating that a highly ordered structure is formed. Figure 8 (c) shows that when the solvent is solution A and chloroform with a total volume / ethanol ratio of 1 / 3, the CPL signal is the strongest, g lumThe value of χ is 0.005, which is attributed to the synergistic effect of multiple weak interactions between chiral limonene and C-1, which transmits the chiral signal to C-1, thereby generating a significant chiral optical response. At the same time, it also shows that the poor solvent driving has a significant effect on the CPL performance of the assembly. The addition of ethanol can adjust the spatial arrangement and stacking mode between molecules, enhance the anisotropy, and thus improve the chiral optical activity.

[0080] Example 3

[0081] A chiral self-assembly material based on the tetraphenylstyrene-carbazole material (C-1) prepared in Example 7 was self-assembled.

[0082] Chiral limonene and C-1 prepared in Example 7 were selected for self-assembly, and the specific experimental design is as follows:

[0083] Solution A: 7 mg of C-1 prepared in Example 7 was weighed and added to 1 mL of chloroform to prepare a stock solution with a concentration of 7 mg / mL.

[0084] Solution B: R-limonene as limonene solution. That is: 100 μL of R-limonene and 0 μL of S-limonene mixed to obtain χ = -100% solution.

[0085] The calculation formula of χ value is as follows:

[0086]

[0087] Wherein, S and R represent the volume of S-limonene and R-limonene, respectively;

[0088] Self-assembly of achiral fluorescent molecule C-1 and chiral limonene: 100 μL of solution A and 100 μL of solution B were mixed uniformly in a reaction bottle, 125 μL of chloroform and 675 μL of ethanol (1 / 3) were added, and after stirring uniformly, the mixture was placed at 15°C until the aggregates appeared.

[0089] At 15°C, left-handed helical flower-like multi-level structures with a diameter of about 145 μm were generated Figure 9 a, c), which were proved to be composed of nanosheet building blocks with a size of about 6 × 3.5 μm Figure 9 b, d)

[0090] The cause of the helical morphology can be traced back to the dual regulation mechanism at the molecular level: the rigidity of the planar tetraphenylstyrene and carbazole groups drives the formation of two-dimensional nanosheets through π-π interaction, and the chiral induction effect of R-limonene breaks the symmetrical arrangement of the nanosheets through intermolecular torque effect, promoting their hierarchical stacking along the helical axis. This cross-scale chiral transmission process ultimately realizes the directional construction of left-handed topology at the macroscopic scale.

[0091] The morphology-dependent optical properties of the C-1 and R-limonene assemblies were revealed by laser scanning confocal fluorescence microscopy (LSCM). Figure 10 ) Petal-shaped spherical aggregates washed with ethanol ( Figure 10 The middle cD) is formed by multiple nanosheets with a thickness of about 15nm (size of about 2×4μm) assembled by edge curling. The overall diameter is about 180μm, and the thickness of the central area reaches 90μm, forming a light shielding effect. Only the outer area can be penetrated by the excitation light, resulting in lower blue light emission intensity than the sheet crystal.

[0092] The self-assembled composite of C-1 and R-limonene was subjected to XC-XRD analysis. After filtration and drying, the sample was subjected to absolute configuration determination and raw diffraction data collection using a Bruker SMARTAPEX(II)-CCD single crystal diffractometer equipped with a copper-palladium light source. After data reduction using APEX3 software, the processed results were imported into the Olex2 program system for structural elucidation and crystallographic information files. The relevant parameters are detailed in Table 2.

[0093] Table 2 R-C-1 single crystal data report

[0094]

[0095] Figure 11 (ac) show the stacking patterns of the crystal along the a, b, and c axes, respectively, indicating that the molecules form a stable layered structure through three-dimensional orderly arrangement. Figure 11 The asymmetric unit in (d) contains C-1 molecule and limonene molecule, and there are BH···HC interactions between the two (bond distance ), indicating that there is a significant intermolecular interaction between C-1 and limonene. This short distance indicates that the electron-deficient characteristics of boron and the electron cloud of methyl hydrogen may form a directional electronic complementarity, thereby driving the specific recognition of host and guest molecules. The two C-C bond lengths in carborane are 1.71 and Standard single key The dihedral angles of tetraphenylethylene exhibit an extremely asymmetric distribution (-138.65° and 12.9°), of which the nearly planar 12.9° dihedral angle may optimize the π-π stacking efficiency by maximizing the conjugation of the benzene rings, while the significantly distorted -138.65° (equivalent to +41.35°) creates space for interlayer filling by releasing intramolecular steric hindrance. Figure 11 (e) Further revealing the interaction between limonene hydrogen and carborane, tetraphenylethylene, etc. in the polymer. Finally, the molecules form a highly periodic layered structure along the stacking direction ( Figure 11 f), the interlayer spacing is precisely stable at Despite the significant difference in local bond length, dihedral angle, etc., the synergistic effect of flexible conformation and rigid skeleton enables the formation of periodic repeat units with almost identical size on macroscopic scale, suggesting the structural tunability and macroscopic stability of such self-assembly system in the design of functional materials.

[0096] Example 4

[0097] Other preparation steps are the same as Example 3, except that the amount of ethanol added is changed (500 μL of ethanol, 675 μL of ethanol), so as to change the total volume of solution A and chloroform / ethanol ratio, and products with total volume of solution A and chloroform / ethanol = 1 / 2, 1 / 3 are prepared.

[0098] Under the kinetic regulation condition at 15℃, both solvent systems form multi-stage flower-like structures Figure 12 ). The average diameter of the assembly of the 1 / 2 solvent system reaches 405.4±12.4 μm Figure 13 a), and the structure is formed by the hierarchical stacking of nanosheets with an edge length of about 12 μm through a hydrogen bond network; the diameter of the assembly under the 1 / 3 system is significantly reduced to 182.1±12.3 μm Figure 13 b), and the edge length of the nanosheet is reduced to 6.5±0.8 μm, indicating that the increase of ethanol ratio affects the assembly through a double mechanism: 1. Reducing the solubility of C-1 accelerates nucleation, resulting in the decrease of the size of the unit; 2. Enhancing the hydrophobic effect induces the interface curling of the nanosheet, forming a high-density three-dimensional hierarchical structure.

[0099] By systematically analyzing the chiral optical properties of the supramolecular assembly of C-1 and R-limonene, the regulation mechanism of the solvent ratio on the circularly polarized luminescence (CPL) performance is revealed. The flower-like aggregate, solution A and chloroform / ethanol = 1 / 2 system shows a red-shifted fluorescence emission at 478 nm Figure 14 a), and the XRD pattern has a stronger diffraction peak than the 1 / 3 system Figure 14 b), indicating that the decrease of ethanol ratio can optimize the assembly kinetics, forming a long-range ordered helical stacking structure. Under this condition, the CPL signal intensity reaches -50, and glum is 9.6×10 -3 -4 -3 ( Figure 14 c-d). The research results show that by precisely regulating the solvent ratio, the glum value can be optimized in the order of 10 -3 ~ 10 -2 , breaking the bottleneck that the glum value of traditional chiral materials is mostly distributed in the order of 10 -4 ~ 10 -3 , and providing a new strategy for the development of high-performance circularly polarized luminescent materials.

[0100] The chemical bond structure and microenvironment of the chiral supramolecular assembly were systematically characterized by Fourier transform infrared spectroscopy. In the experiment, the chiral assembly sample (1 / 2) after solvent washing and vacuum drying was pressed into a pellet with potassium bromide and the pellet was observed at 4000-500 cm -1 Wave number range for infrared spectrum test. Figure 15 (ad) shown, 1645cm -1 The characteristic peak at corresponds to the C=C double bond vibration mode in the limonene molecule, which is completely absent in the spectrum of the C-1 monomer molecule, confirming that the monomer molecule itself does not contain this structural unit. Notably, the C=C double bond characteristic peak is significantly enhanced in the spectrum of the S / R supramolecular assembly, strongly confirming the participation of chiral limonene molecules in the assembly process. Mechanistic studies have shown that the olefinic double bond of limonene promotes the directional growth of the supramolecular assembly through non-covalent bonds such as π-π interactions and van der Waals forces with the C-1 molecule. At the same time, the spatial orientation control of the monomer molecules induced by the chiral center of limonene achieves molecular-level chirality transfer, thereby forming a supramolecular assembly system with a stable three-dimensional structure.

[0101] The thermodynamic behavior of C-1 monomer and its supramolecular aggregates assembled with S / R-limonene (1 / 2) was systematically studied by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Under nitrogen protection, TGA tests at a heating rate of 10°C / min from room temperature to 700°C showed that C-1 monomer only suffered a 2% mass loss at 479°C and a cumulative loss of 5% at 514°C, indicating that it has excellent thermal stability ( Figure 16 In the comparative experiment, the assembly system containing limonene showed significant mass loss around 175℃ ( Figure 16 c), this temperature range is highly consistent with the boiling point of limonene (175-177℃), and it is speculated that the sudden drop in mass at this stage is due to the volatilization or thermal decomposition of limonene molecules. Further DSC analysis (heating / cooling rate 20℃ / min, temperature range room temperature-300℃-room temperature) found that C-1 showed an endothermic peak at 204℃ ( Figure 16 b), which once again verifies its thermal stability; and the two chiral supramolecular assembly systems show a stronger endothermic peak at 286 ° C ( Figure 16 In (d), it is speculated that the introduction of chiral limonene significantly improves the crystalline order of the assembly system by enhancing the intermolecular non-covalent interactions (such as π-π stacking or chiral induction effect), thereby forming a supramolecular network structure with higher thermal stability.

[0102] Example 5

[0103] Self-assembly at different enantiomeric excess values

[0104] Solution A: 7 mg of C-1 was weighed and dissolved in 1 mL of chloroform to prepare a stock solution with a concentration of 7 mg / mL.

[0105] Solution B: S-limonene and R-limonene were mixed to obtain limonene solutions with different enantiomeric excess values χ.

[0106] The formula for calculating χ value is as follows:

[0107]

[0108] Wherein, S and R represent the volume of S-limonene and R-limonene respectively.

[0109] Self-assembly of C-1 with chiral limonene: 100 μL of solution A and 120 μL of solution B were mixed uniformly, 660 μL of ethanol and 120 μL of chloroform were added, and the mixture was left to stand at 15 or 25°C until the aggregates appeared.

[0110] In solution B, S-limonene and R-limonene were mixed to obtain limonene solutions with different enantiomeric excess values χ: a gradient of ±100, ±80, ±60, ±40, ±20, 0% was selected for comparison;

[0111] Wherein, ±100: 100 μL of S-limonene and 0 μL of R-limonene were mixed to obtain χ = +100% solution; 100 μL of R-limonene and 0 μL of S-limonene were mixed to obtain χ = -100% solution.

[0112] ±80: 90 μL of S-limonene and 10 μL of R-limonene were mixed to obtain χ = +80% solution; 90 μL of R-limonene and 10 μL of S-limonene were mixed to obtain χ = -80% solution.

[0113] ±60: 80 μL of S-limonene and 20 μL of R-limonene were mixed to obtain χ = +60% solution; 80 μL of R-limonene and 20 μL of S-limonene were mixed to obtain χ = -60% solution.

[0114] ±40: 70 μL of S-limonene and 30 μL of R-limonene were mixed to obtain χ = +40% solution; 70 μL of R-limonene and 30 μL of S-limonene were mixed to obtain χ = -40% solution.

[0115] ±20: 60 μL of S-limonene and 40 μL of R-limonene were mixed to obtain χ = +20% solution; 60 μL of R-limonene and 40 μL of S-limonene were mixed to obtain χ = -20% solution.

[0116] ±0: Mixing 50 μL of S-limonene and 50 μL of R-limonene gives a solution with χ = +0%; mixing 50 μL of R-limonene and 50 μL of S-limonene gives a solution with χ = -0%.

[0117] The assembly system of C-1 and chiral limonene can form two morphological structures of different complexity, and their formation mechanisms are significantly different. In order to explore how chirality drives the evolution of nano-units into multi-level structures, the experiment systematically studied the effects of chiral enantiomeric excess (χ) and nucleation temperature (tn) on the assembly morphology. By adjusting the χ value of limonene (from completely racemic state χ = 0 to single chiral excess state χ = ± 100) and the initial assembly temperature t n , combined with scanning electron microscopy ( Figure 17 ) dynamic tracking of morphological evolution. The results show that under the condition of constant reactant concentration, only changing χ and t n A continuous morphological transition from simple crystals to complex hierarchical structures can be obtained, which provides key experimental evidence for revealing the chiral regulation mechanism.

[0118] In the co-assembly system of C-1 and chiral limonene, the chiral molecules restructure intermolecular forces through stereochemical encoding, driving the morphology from two-dimensional sheets to multi-level superstructures. The underlying mechanism is the synergistic interaction between the chiral molecules and the achiral host material, which triggers symmetry breaking and regulates the thermodynamic-kinetic equilibrium path.

[0119] When χ = 0, symmetry-dominated π-π stacking (carbazole planes) and the hydrophobic interaction of the rigid carborane backbone form homogeneous two-dimensional plate-like crystals with isotropic molecular arrangement and the lowest free energy. When χ = ±20, the stereoelectronic effects of chiral limonene (such as the asymmetric van der Waals contact between the S-methyl group and the tetraphenylethylene benzene ring) induce local tilting of the carbazole plane, disrupting the original symmetric stacking pattern and promoting preferential growth at the crystal edge, manifesting as primary complexity.

[0120] At a critical threshold of χ = ±40, the chirality-induced effect becomes global: the π-π interaction between the limonene double bond and tetraphenylethylene drives the molecular helical twisting around the carborane, forming chirally oriented (S right-handed / R left-handed) curvature nanosheets. Driven by this interaction, the nanosheets stack in a "petal-stamen" hierarchy. The carborane rigidity constrains the distortion while promoting fractal growth through stress accumulation, constructing a flower-like hierarchical structure. At χ > ±40, chirality saturation triggers interfacial reconstruction: the excess limonene hydrophobic tails form a dense monolayer at the nanosheet interface. The long-range chiral field forces the petals to extend radially along the helical axis. The dynamic mismatch between the edge hydrogen bond-fixed conformation and the continuous π-π adjustment of the center drives secondary curling (e.g., an S-shaped + 100 nested structure), further increasing the complexity.

[0121] For different t n The performance of the assembly was characterized under the conditions of χ and χ.Figure 18 (ac) are the fluorescence and circularly polarized light spectra of the assembly under different χ conditions at 30°C. Figure (a) shows that the aggregate emits blue light with the fluorescence emission peak at 480nm. Figure (b) CPL spectrum shows that when χ = 0, the system is in a symmetrical state, the intermolecular interactions are uniform and highly ordered, the symmetry inhibits the expression of chiral optical activity, and the CPL signal is 0; as χ increases or decreases, the absolute value of the CPL signal of the aggregate gradually increases, and the asymmetry of the chiral molecules gradually increases, breaking the symmetrical balance of the intermolecular interactions, causing the assembly morphology to change from a simple crystal structure to a multi-level structure, which not only increases the surface area of ​​the assembly, but also enhances the synergistic effect between chiral molecules. The highly ordered development between molecules forms a three-dimensional helical structure, which further enhances the CPL signal. Figure 18 (df) are the fluorescence and circularly polarized light spectra of the assembly under different χ conditions at 40°C. At this temperature, the assembly emits blue light with a fluorescence emission peak at 470nm. The CPL spectrum shows that when χ = 0, the CPL signal is 0; as χ increases or decreases, the absolute value of the CPL signal of the aggregate gradually increases, and the asymmetry of the chiral molecule gradually increases. Figure 18 (gi) is the fluorescence and circularly polarized light spectra of the assembly under different χ conditions at 50°C. At this temperature, the fluorescence emission peak of the assembly is located at 470nm, and the CPL signal change is the same as the previous two groups, which is consistent with expectations. Figure 18 (jl) for different t n The XRD test of the assembly under the conditions of χ and χ shows that the assembly has strong diffraction peaks, indicating that the aggregates have good crystallinity.

[0122] Example 6

[0123] Self-assembly under different chiral reagents

[0124] The other methods are the same as those in Example 1, which are based on the self-assembly method of C-1 material (tetraphenylethylene-carbazole-carborane) and limonene, except that the temperature is room temperature (15°C), chiral reagents such as β-pinene, S / R-carvone, vitamin D2, and valencia orangene are used for the assembly experiment, and the resulting aggregates are washed three times with ethanol and water and then placed on a silicon wafer for SEM morphology characterization ( Figure 19 ).

[0125] SEM characterization shows that all chiral compounds form three-dimensional hierarchical structures with C-1 by nanosheet aggregation, and the core driving force is the multi-level synergy of chiral molecules and C-1. The unique cyclic skeleton, double bond and functional groups of chiral reagents such as carbonyl can construct primary assembly units through non-covalent interactions such as π-π stacking and hydrogen bonding, and the chiral center induces stereoselective arrangement (such as helical / laminar chiral superstructure). The rigid tetraphenyl ethylene plane of C-1 material provides support for nanosheet skeleton, the electron-rich properties of carbazole enhance the π-π stacking strength, and the hydrophobicity of carborane stabilizes the assembly interface, all of which synergistically give the system unique structure guiding ability. This multi-level assembly mechanism of “chiral induction-rigid skeleton anchoring-electronic synergy” reveals the special value of C-1 material in constructing complex supramolecular topology.

[0126] PL and CPL spectrum tests are performed on the assembly to explore the degree of CPL signal amplification of the chiral reagent. Figure 20 (a) shows that the fluorescence emission peaks of the aggregate are located at 492, 514, 497, 498 and 503 nm, and the difference in emission peak position is mainly due to the difference in the unique stereostructure, functional group characteristics of each chiral molecule and the interaction mode between the tetraphenyl ethylene-carbazole-carborane material, thereby causing specific changes in the molecular arrangement, electronic structure and excited state characteristics of the assembly. Figure 20 (b) and (c) are the CPL spectrum and g lum value of each assembly, it can be seen that the chiral signal transfer of several chiral reagents and C-1 is successful, the CPL signal of the assembly of C-1 and valencian orange is the strongest, and the g lum value reaches 0.01, which may be that the rigid polycyclic structure of valencian orange can further stabilize the chiral configuration of the assembly through the steric hindrance effect, reduce the non-radiative relaxation path, and thereby enhance the intensity of the CPL signal.

[0127] In summary, the non-chiral fluorescent compound C-1 is prepared, and tests show that the C-1 material has good thermal stability, electrochemical property and crystallinity. The chiral limonene is selected as a chiral template to self-assemble with the C-1 material at different temperatures and in different solvents to form two-dimensional sheet structure and complex three-dimensional flower-like structure. The influence of the rigidity, electron-rich properties and hydrophobicity of carborane of the C-1 molecule on the supramolecular self-assembly is studied in depth through scanning electron microscopy, fluorescence, circularly polarized light, SC-XRD and powder XRD tests, and the internal mechanism of the chiral transfer of chiral limonene and C-1 is explored. The successful coupling between chiral limonene and C-1 molecules increases the order of molecular stacking from a macroscopic level, greatly improves the circular polarization value, provides a powerful structural model and theoretical basis for the structure-activity relationship between the structure of the organic supramolecular assembly and the circularly polarized fluorescence, and provides a new strategy for designing new organic circularly polarized photoelectric materials.

[0128] Example 7

[0129] The chemical reagents used in the experiments are listed in Table 1.

[0130] Table 1 Chemical reagents and drugs used in the experiments

[0131] Reagent name Purity Manufacturer Methanol 99% Shanghai Aneyi Chemical Reagent Co., Ltd. Ethanol 99% Shanghai Aladdin Bio-Chem Technology Co., Ltd. Tetrahydrofuran 109-99-9 Shanghai Aneyi Chemical Reagent Co., Ltd. Triethylamine 121-44-8 Shanghai Aneyi Chemical Reagent Co., Ltd. Toluene 108-88-3 Nanjing Runsheng Petrochemical Co., Ltd. Tetrakis(triphenylphosphine)palladium 14221-01-3 Henan Alpha Chemicals Co., Ltd. Cuprous iodide 7681-65-4 Henan Alpha Chemicals Co., Ltd. Sodium hydroxide 1310-73-2 Shanghai Nation Reagent Co., Ltd. Hydrochloric acid 7647-01-0 Shanghai Nation Reagent Co., Ltd. (S)-(-)-1,1'-bi(2-naphtol) 18531-99-2 Henan Alpha Chemicals Co., Ltd. (2-(4,6-diphenyl-1,3,5-triazin-yl)phenyl)boronic acid 31574-87-5 Shanghai Aladdin Bio-Chem Technology Co., Ltd. 2-(3,5-dibromophenyl)-4,6-diphenyl-1,3,5-triazine 1073062-59-5 Henan Alpha Chemicals Co., Ltd. 9'-(4-bromophenyl)-9'H-9,3':6',9"-tris-carbazole 57102-42-8 Wuxi Yasheng Chemical Co., Ltd. Decaborane 17702-41-9 Wuxi Yasheng Chemical Co., Ltd. N,N-dimethylaniline 121-69-7 Tianjin Xins Biochemical Technology Co., Ltd.

[0132] Toluene is dried and equipped with molecular sieve, tetrahydrofuran is equipped with molecular sieve, and the water content is ≤20 ppm. The specific synthesis steps of the target product based on tetraphenyl ethylene-carbazole material are as follows.

[0133]

[0134] (1) Synthesis of intermediate product 2: Take drug 1 (1.14 g, 1.99 mmol), an appropriate amount of CuI catalyst (5% of the mass of drug 1), and tetraphenylphosphine palladium catalyst (10% of the mass of drug 1) and add them to a 250 mL double-necked round-bottom flask under light protection and nitrogen protection, vacuumize and fill with nitrogen at least three times, add anhydrous and oxygen-free triethylamine (Et3N) 60 mL, add phenylacetylene (3.0 mL, 27.32 mmol, 0.93 g / mL) under water bath stirring conditions, warm up to 75°C, avoid light and react for about 12 h, after complete reaction is monitored by TLC spotting plate, cool the reaction liquid to room temperature, and remove the solvent with a vacuum rotary evaporator. Extract the residue with dichloromethane three times, combine the organic phase, and remove the solvent by rotary evaporation. Purify by column chromatography to obtain intermediate product 2 (1.04 g, yield 85%).

[0135] (2) Synthesis of intermediate product 3: Take carborane (0.55 g, 4.5 mmol) in a double-necked round-bottom flask, vacuumize, take a mixture of N,N-dimethylaniline (2.4 g, 19.5 mmol) and toluene (60 mL) as a solvent, inject into the reaction bottle after nitrogen blowing, avoid light, place the reaction bottle in a constant temperature oil bath, stir at room temperature for 30 min, warm up to 70°C, react for 2 h, and cool down to 40°C. Dissolve the dried intermediate product 2 (1.04 g, 1.99 mmol) in toluene (60 mL), inject into the reaction bottle after nitrogen blowing, warm up to 115°C, react for 12 h, and cool down to room temperature after complete reaction is monitored by TLC spotting plate. Remove the solvent by rotary evaporation, extract the residue with dichloromethane (3 x 100 mL), separate the organic layer, remove the solvent by rotary evaporation, and purify by column chromatography to obtain white powder product 3 (1.25 g, yield 82%).

[0136] (3) Synthesis of target product tetraphenylstyrene-carbazole material: the reaction step is the same as that of synthesis of intermediate product 2, and the product 3 of the medicine 1 is separated and purified by column chromatography to obtain 1.26 g of the target product tetraphenylstyrene-carbazole material, with a yield of 75%. 1 H NMR (400 MHz, Chloroform-d) δ 8.11 (d, J = 2.0 Hz, 1H), 7.66-7.59 (m, 1H), 7.52 (dd, J = 7.2, 1.8 Hz, 2H), 7.47 (dd, J = 8.9, 2.0 Hz, 1H), 7.33-7.24 (m, 3H), 7.19 (dd, J = 8.3, 6.1 Hz, 1H), 7.14 (d, J = 3.7 Hz, 2H), 7.15-6.99 (m, 10H). 13 CNMR (101 MHz, CDCI3) δ 143.49, 142.37, 142.36, 142.23, 140.88, 140.55, 139.08, 134.60, 132.08, 130.46, 130.33, 130.31, 130.24, 130.00, 129.86, 129.72, 129.11, 128.03, 127.29, 126.82, 126.76, 126.67, 125.69, 125.64, 125.41, 122.56, 122.44, 122.18, 121.62, 119.38, 108.53, 90.25, 87.27, 85.29, 84.74, 76.30, 76.19, 75.99, 75.67. 11 B NMR (128 MHz, CDCI3) δ -2.15, -2.77, -10.71.

[0137] The crystal structure and crystallization properties of the product based on tetraphenylstyrene-carbazole material were systematically characterized by powder X-ray diffraction (PXRD) technology, and the test conditions were room temperature. It can be found from Figure 1 that the material has a very obvious characteristic peak at a diffraction angle of 28°, indicating that the material has a highly ordered lattice arrangement and excellent crystalline integrity. The crystal form of the material can form a stable crystal state stacking.

[0138] The electrochemical performance of the product based on the tetraphenylstyrene-carbazole material was systematically evaluated. Using a three-electrode standard test system, the energy storage characteristics were characterized by cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) techniques. The preparation process of the working electrode includes: taking the tetraphenylstyrene-carbazole material active material with a mass fraction of 85% as the core component, cooperating with 10% carbon black to construct a conductive network, and 5% polytetrafluoroethylene (PTFE) as a binder, and forming a homogeneous slurry by ethanol solvent assisted grinding; then the composite slurry is accurately coated on the pretreated nickel foil substrate (effective area 1cm 2 ), and cured and formed by vacuum drying at 80°C for 24 hours. This design strategy realizes the balance optimization of charge transfer efficiency and mechanical stability through the synergistic effect of active material, conductive agent and binder.

[0139] The electrochemical spectrum of the tetraphenylstyrene-carbazole material is shown in Figure 2 The CV curve shows that the oxidation-reduction peak shape of the tetraphenylstyrene-carbazole material remains highly symmetrical at a wide range of scan rates of 30-200mV / s, and the integral area increases regularly with the increase of scan rate, indicating that it has fast charge transfer dynamics and stable electrochemical reversibility. The synchronous GCD test (1-4A / g current density gradient) further verifies that the material maintains the typical double-layer characteristics while showing a significantly extended discharge platform, corresponding to a specific capacitance value of 326F / g (1A / g), and the capacitance retention rate remains above 82% as the current density doubles. The high consistency of CV and GCD data confirms that the tetraphenylstyrene-carbazole material has high specific capacity characteristics and excellent rate performance, providing key experimental evidence for its application in energy storage devices.

[0140] It should be noted that in this paper, relationship terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between the entities or operations. Moreover, the terms "include", "contain" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed or inherent to such process, method, article or equipment.

[0141] It should be noted that the above only illustrates the technical idea of the present application, and cannot limit the protection scope of the present application. For ordinary skilled persons in the technical field, without departing from the principles of the present application, a number of improvements and refinements can be made, which fall within the protection scope of the claims of the present application.

Claims

1. A chiral self-assembly material based on tetraphenylethylene-carbazole material, characterized in that: The chiral self-assembly material is mainly prepared by self-assembly of a chiral reagent and an achiral fluorescent molecule; The achiral fluorescent molecule is a tetraphenylethylene-carbazole material, and its structure is shown in Formula 1: The chiral reagent is limonene.

2. The self-assembly method of the chiral self-assembly material based on tetraphenylethylene-carbazole material according to claim 1, characterized in that: The following steps are involved: S01, dissolving the achiral fluorescent molecule represented by Formula 1 in chloroform to obtain solution A; S02, mixing S-limonene and R-limonene to obtain a limonene solution with an excess value x, i.e., solution B; The calculation formula of χ value is as follows: Where S is the volume of S-limonene and R is the volume of R-limonene; S03. Mix solution A and solution B evenly, add ethanol and chloroform, stir evenly, and let stand at 15-50°C until aggregates appear, thereby obtaining a chiral self-assembled material.

3. The self-assembly method of a chiral self-assembly material based on tetraphenylethylene-carbazole material according to claim 2, characterized in that: In step S01 , the concentration of the achiral fluorescent molecule in solution A is 7.1-7.2 mg / mL.

4. The self-assembly method of a chiral self-assembly material based on tetraphenylethylene-carbazole material according to claim 2, characterized in that: In step S02 , the ratio of S to R is ±100%.

5. The self-assembly method of a chiral self-assembly material based on tetraphenylethylene-carbazole material according to claim 2, characterized in that: In step S03, the volume ratio of the total volume of solution A and chloroform to that of ethanol is 1:2-3.

6. The self-assembly method of a chiral self-assembly material based on tetraphenylethylene-carbazole material according to claim 2, characterized in that: In step S03, the volume ratio of solution A to solution B is 1:1-1.

2.

7. A method for preparing a tetraphenylethylene-carbazole material, characterized in that: The preparation method comprises the following steps: (1) Synthesis of intermediate product 2: Under the protection of nitrogen and light-proof, add drug 1, CuI catalyst and tetrakistriphenylphosphine palladium catalyst to a reaction vessel, evacuate and fill with nitrogen at least three times, add anhydrous and oxygen-free triethylamine or a mixed solution of tetrahydrofuran and triethylamine, and phenylacetylene, raise the temperature to 70-75°C, and react in the dark for 8-12 hours. Cool the reaction solution to room temperature, remove the solvent by rotary evaporation, and extract the residue with dichloromethane three times. Combine the organic phases, remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain intermediate product 2; (2) Synthesis of intermediate product 3: Carborane was placed in a reaction vessel and vacuum treated. A mixed solvent of N,N-dimethylaniline and toluene was taken, nitrogen was blown, and then injected into the reaction vessel, protected from light, stirred at room temperature for 25-30 min, heated to 70-75°C, reacted for 1-2 h, cooled to 35-40°C, dried intermediate product 2 was dissolved in toluene, nitrogen was blown, and then injected into the reaction flask, heated to 110-120°C, reacted for 8-12 h, and after complete reaction, cooled to room temperature, and the solvent was removed by rotary evaporation. The residue was extracted with dichloromethane, the organic layer was separated, the solvent was removed by rotary evaporation, and the product 3 was separated and purified by column chromatography to obtain a white powder product 3; (3) Synthesis of the target product: Under the protection of nitrogen and light-proof, add the drug 3, CuI catalyst and tetrakistriphenylphosphine palladium catalyst to a reaction vessel, evacuate and fill with nitrogen at least three times, add anhydrous and oxygen-free triethylamine or a mixed solution of tetrahydrofuran and triethylamine, and phenylacetylene, raise the temperature to 70-75°C, and react in the dark for 8-12 hours. Cool the reaction solution to room temperature, remove the solvent by rotary evaporation, and extract the residue with dichloromethane three times. Combine the organic phases, remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain the target product.

8. The preparation method of tetraphenylethylene-carbazole material according to claim 8, characterized in that: In step (1), the molar ratio of drug 1 to phenylacetylene is 1:13-14, the mass percentage of CuI catalyst to drug 1 is 5%, and the mass percentage of tetrakistriphenylphosphine palladium catalyst to drug 1 is 10%; the mass volume ratio of drug 1 to triethylamine or a mixed solution of tetrahydrofuran and triethylamine is 1:50-55; the ratio of tetrahydrofuran to triethylamine in the mixed solution of tetrahydrofuran and triethylamine is 1:3; In step (3), the molar ratio of drug 3 to phenylacetylene is 1:13-14, the mass percentage of CuI catalyst to drug 3 is 5%, and the mass percentage of tetrakistriphenylphosphine palladium catalyst to drug 3 is 10%; the mass volume ratio of drug 3 to triethylamine or a mixed solution of tetrahydrofuran and triethylamine is 1:50-55; and the ratio of tetrahydrofuran to triethylamine in the mixed solution of tetrahydrofuran and triethylamine is 1:

3.

9. The method for preparing a tetraphenylethylene-carbazole material according to claim 8, characterized in that: In step (2), the molar ratio of carborane to intermediate product 2 is 2-3:1, the molar ratio of carborane to N,N-dimethylaniline is 1:4-5, and the mass volume ratio of N,N-dimethylaniline to toluene is 1:

25.

10. A tetraphenylethylene-carbazole material prepared by the preparation method according to any one of claims 7 to 9, as shown in Formula 1: